Investigation of the thermal removal steps of capping agents in the synthesis of bimetallic iridium-based catalysts for the ethanol oxidation reaction. Issue 1 (16th December 2020) - Prössl, Carolin; Kübler, Markus; Nowroozi, Mohammad Ali; Paul, Stephen; Clemens, Oliver; Kramm, Ulrike I.
Abstract : Two iridium-based catalysts (namely IrSn and IrNi) are synthesised via a polyol route involving capping agents. Abstract : Two iridium-based catalysts (namely IrSn and IrNi) are synthesised via a polyol route involving capping agents. The capping agents are removed according to a time-consuming multistep heat-treatment protocol described in the literature (N2 → N2 /O2 → H2 ). In this work the effect of each of these steps on the structural composition and catalytic activity is investigated by X-ray diffraction (XRD), transmission electron microscopy (TEM), Fourier-transform infrared spectroscopy (FT-IR), X-ray photoelectron spectroscopy (XPS) and electrochemistry. It is shown that heating in nitrogen is not required, whereas air is the most effective for the removal of the capping agents. Besides FT-IR, the analysis of sp 3 carbon (from XPS) turned out to give reasonable insights into capping agent removal. Induced by hydrogen treatment no further change of the surface occurs, while particles tend to grow and become more crystalline. While structural changes are similar for both catalysts, the impact of each of the steps on the catalysis is different: the activity per gram of iridium becomes even lower for IrSn (an electrochemical cleaning agent that was used as reference measurements, seems best suited) while the activity is doubled for the IrNi case. Our results illustrate that the selection of the cleaning procedure strongly depends on the investigated system and should be optimised individually.